Perfusion and apparent oxygenation in the human placenta (PERFOX). Issue 2 (21st August 2019) - Hutter, Jana; Harteveld, Anita A.; Jackson, Laurence H.; Franklin, Suzanne; Bos, Clemens; van Osch, Matthias J. P.; O'Muircheartaigh, Jonathan; Ho, Alison; Chappell, Lucy; Hajnal, Joseph V.; Rutherford, Mary; De Vita, Enrico
Abstract : Purpose: To study placental function—both perfusion and an oxygenation surrogate ( T 2 * )—simultaneously and quantitatively in‐vivo. Methods: Fifteen pregnant women were scanned on a 3T MR scanner. For perfusion measurements, a velocity selective arterial spin labeling preparation module was placed before a multi‐echo gradient echo EPI readout to integrate T 2 * and perfusion measurements in 1 joint perfusion‐oxygenation (PERFOX) acquisition. Joint motion correction and quantification were performed to evaluate changes in T 2 * and perfusion over GA. Results: The optimized integrated PERFOX protocol and post‐processing allowed successful visualization and quantification of perfusion and T 2 * in all subjects. Areas of high T 2 * and high perfusion appear to correspond to placental sub‐units and show a systematic offset in location along the maternal‐fetal axis. The areas of highest perfusion are consistently closer to the maternal basal plate and the areas of highest T 2 * closer to the fetal chorionic plate. Quantitative results show a strong negative correlation of gestational age with T 2 * and weak negative correlation with perfusion. Conclusions: A strength of the joint sequence is that it provides truly simultaneous and co‐registered estimates of local T 2 * and perfusion, however, to achieve this, the time per slice is prolonged compared to a perfusion only scan which can potentially limit coverage. The achieved interlocking can be particularly useful when quantifying transient physiological effects such as uterine contractions. PERFOX opens a new avenue to elucidate the relationship between maternal supply and oxygen uptake, both of which are central to placental function and dysfunction.